Perinatal health in peruvians and migrants, according to the registry of vital events data, Peru 2018 - Asencios-Falcón, Evelyn Margott (2023)
Objective: To relate three adverse perinatal outcomes and maternal migratory status, Perú 2018. Material and methods: Secondary analysis of 484,533 data from the Vital Facts Registration System of Peru (RHV) of the year 2018, of which 476,471 were Peruvian and 8,062 migrants. The dependent variables were preterm delivery, cesarean section, and low birth weight; which were associated with the main independent variable (nationality of the mother) and with three sociodemographic variables (age, educational level and occupation of the mother) and duration of pregnancy is included as an independent variable. Results: The migrants were younger (26.92±5.97 years), with better education (82.7% of ≥10 years of study) and mostly housewives (88.2%). The adjusted model found a statistically significant association between preterm birth and being a migrant (RPa 1,29; IC95% 1,15-1,34), elderly (RPa 1,45; IC95% 1,41-1,49) and professional (RPa 1,26; IC95% 1,21-1,31). Between the cesarean section and being a migrant (RPa 1,17; IC95% 1,14-1,20), elderly (RPa 1,26; IC95%  1,25-1,27), professional (RPa 1,62; IC95% 1,60-1,63) and with preterm pregnancy (RPa: 1,61; IC95%  (1,60-1,63). Between low birth weight and being a migrant (RPa: 1,40; IC95% 1,32-1,50), adolescent (RPa: 1,26; IC95% 1,22-1,29), having less than 6 years of study (RPa: 1,33; IC95% 1,30-1,40) and with preterm pregnancy (RPa: 24,98; IC95% 24,42-25,55). Conclusions: the nationality of the mother was associated with the three outcome variables. Being a migrant mother in Peru gives a greater probability of having preterm labor, cesarean delivery and newborns with low birth weight; adjusted for age group, level of education, occupation of the mother and duration of pregnancy.